2021
DOI: 10.12998/wjcc.v9.i30.9144
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous diagnosis and treatment of acute myeloid leukemia and chronic lymphocytic leukemia: Two case reports

Abstract: BACKGROUND The concurrence of acute myeloid leukemia (AML) and chronic lymphocytic leukemia (CLL) is rare. Previous reports of such cases have focused mainly on clinical diagnosis and characteristics, so the mechanism remains unclear, and therapy options have been poorly explored. CASE SUMMARY Here, we report two cases of synchronous AML and CLL. Flow cytometry revealed two distinct abnormal cell populations (myeloblasts and lymphoid cells) according to scatter characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…AML and CLL were defined based on the latest World Health Organization classification (12,13), and patients who had any history of exposure to chemotherapy or radiation were excluded. The clinical information of all patients is displayed in Table I (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). Results from the studies demonstrated a higher incidence of concurrent untreated CLL and AML in older individuals, with a median patient age at diagnosis of AML of 69 years (range, 52-86 years).…”
Section: Discussionmentioning
confidence: 99%
“…AML and CLL were defined based on the latest World Health Organization classification (12,13), and patients who had any history of exposure to chemotherapy or radiation were excluded. The clinical information of all patients is displayed in Table I (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). Results from the studies demonstrated a higher incidence of concurrent untreated CLL and AML in older individuals, with a median patient age at diagnosis of AML of 69 years (range, 52-86 years).…”
Section: Discussionmentioning
confidence: 99%